1998
DOI: 10.1007/bf03043008
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient coronary angiography: Indications, safety, and complication rates

Abstract: In the years since the introduction of outpatient cardiac catheterization and coronary angiography, the indications for the use of these procedures have expanded rapidly with advancements in surgical and endovascular procedures. The safety of outpatient coronary angiography has been well established, comparing very favorably with that of inpatient procedures. At present, a variety of different outpatient facilities exist. Catheterization laboratories may adjoin a hospital or be free-standing; the safety and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 32 publications
0
7
0
2
Order By: Relevance
“…2 Atherosclerotic thromboembolism due to catheter manipulation, thrombus formation in the catheter lumen, and air embolism are the main causes of symptomatic or asymptomatic thromboembolic events. 1 Silent embolic cerebral infarction (SECI) is defined as an embolic origin brain lesion, which is the result of vascular occlusion diagnosed incidentally by magnetic resonance imaging (MRI) or computed tomography (CT) in otherwise healthy participants or at autopsy. 3 Retrospective studies demonstrated that SECI was detected in 13% to 22% of cases undergoing diagnostic coronary angiography (CAG) and percutaneous coronary intervention (PCI).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Atherosclerotic thromboembolism due to catheter manipulation, thrombus formation in the catheter lumen, and air embolism are the main causes of symptomatic or asymptomatic thromboembolic events. 1 Silent embolic cerebral infarction (SECI) is defined as an embolic origin brain lesion, which is the result of vascular occlusion diagnosed incidentally by magnetic resonance imaging (MRI) or computed tomography (CT) in otherwise healthy participants or at autopsy. 3 Retrospective studies demonstrated that SECI was detected in 13% to 22% of cases undergoing diagnostic coronary angiography (CAG) and percutaneous coronary intervention (PCI).…”
Section: Introductionmentioning
confidence: 99%
“…As an invasive diagnostic and therapeutic procedure, there are important periprocedural complications. 1 One of the well-known serious complication category is thromboembolic events including cerebrovascular events. 2 Atherosclerotic thromboembolism due to catheter manipulation, thrombus formation in the catheter lumen, and air embolism are the main causes of symptomatic or asymptomatic thromboembolic events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a review of the literature, the safety of performing diagnostic studies in a mobile laboratory in rural areas has been described by only very few groups. [1][2][3] Thus, our objective was to determine the safety of performing cardiac catheterizations, including left and right heart catheterizations, post-CABG catheterizations, and catheterization of patients with valvular or congenital heart disease, in a mobile laboratory at small community hospitals, provided that emergency helicopter and/or paramedic ambulance service to a tertiary hospital was available.…”
Section: Introductionmentioning
confidence: 99%
“…Although cardiac catheterization is considered a safe invasive procedure, 1 there is always concern about periprocedural complications, including cerebral embolic events. Stroke, determined as a neurological deficit of new onset, is a rare complication (0.11%-0.38%) in patients undergoing cardiac catheterization, but asymptomatic cerebral infarction seems to occur more frequently (12%-23%).…”
mentioning
confidence: 99%